2017
DOI: 10.5688/ajpe6034
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Learner Metacognition in a Professional Pharmacy Elective Course

Abstract: Objective. To investigate the effect of strategic feedback and metacognitive processes on learners' ability to predict performance and improve self-awareness. Methods. Strategic faculty and peer feedback, as well as self-assessments, were implemented in a professional pharmacy elective course throughout the semester, focused on three case-based oral presentations. After each presentation, students utilized an objective rubric to determine self-predicted and peer-predicted scores. Actual scores from faculty wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 24 publications
1
23
1
Order By: Relevance
“…1 In several studies, pharmacy learners have been found to overestimate their performance when compared to the results on evaluations conducted by faculty members or preceptors. [4][5][6][7] This is consistent with findings in medical and nursing students. 8,9 Additionally, top performers have been found to more accurately predict or evaluate their performance than bottom (third or fourth quartile) performers in studies of pharmacy and medical students, and underperformers tend to highly overestimate their knowledge and skills.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…1 In several studies, pharmacy learners have been found to overestimate their performance when compared to the results on evaluations conducted by faculty members or preceptors. [4][5][6][7] This is consistent with findings in medical and nursing students. 8,9 Additionally, top performers have been found to more accurately predict or evaluate their performance than bottom (third or fourth quartile) performers in studies of pharmacy and medical students, and underperformers tend to highly overestimate their knowledge and skills.…”
Section: Introductionsupporting
confidence: 91%
“…Previous studies have shown that learners frequently have poor self-assessment skills and thus, likely poor metacognition skills. [4][5][6][7]13 This is often demonstrated by a poor correlation between student self-assessments and preceptor evaluations and has been demonstrated in many of the health professions, including medicine, nursing, and pharmacy. 4,10,13,14 There are limited data assessing the development of metacognition over time, particularly during APPEs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a body of evidence that has shown knowledge acquisition and retention can be enhanced if a course is designed to include elements crucial to the development and practice of metacognition, [14][15][16][17][18][19][20] including critical thinking, self-directed activities, repetition, [21][22][23] problem solving, 16,18 and reflection. [24][25][26][27][28] In addition, research suggests people become experts in a subject by learning to solve problems that become progressively more complex over time. 29 The inclusion of higher-order thinking elements prepares the students much more effectively for the role of a compounding pharmacist.…”
Section: Discussionmentioning
confidence: 99%